First-line treatment with hepatic arterial infusion plus capecitabine vs capecitabine alone for elderly patients with unresectable colorectal liver metastases. Issue 1 (2nd January 2016) - Li, Xiaodong; Shi, Liangrong; Wu, Jun; Ji, Mei; Zhao, Jiemin; Qiang, Weiguang; Ding, Wenge; Jiang, Jingting; Lu, Qicheng; Wu, Changping
ABSTRACT: This study aimed to compare the efficacy and safety of HAI fluoropyrimidine (FUDR)/capecitabine or single capecitabine as first-line treatment for elderly patients with unresectable colorectal liver metastases (CLMs). Fifty-one elderly patients with liver-only CLMs were eligible for enrollment. Patients were divided into HAI FUDR /capecitabine group and single capecitabine group randomly. The primary endpoint was median survival time (MST), defined as the time from the date of catheter implantation to the date of death or the date of the last follow-up. The secondary endpoint was objective antitumor response and adverse events. The HAI pump was implanted before chemotherapy. All patients received a 3-week cycle of oral capecitabin. In Group A, the RR and DCR were both 95.8%. In Group B, the RR and DCR were 48.1% and 81.5%, respectively. There was significant difference between the RRs of the 2 groups ( P < 0.001). But there was no significant difference between the DCRs of the 2 groups ( P = 0.053). There was a statistical difference between the MSTs of the 2 groups (18.5 vs. 13 months, P = 0.0312). HAI FUDR combined with oral capecitabine as the first-line treatment for elderly patients with CLMs has promising efficacy and safety.